"Weak State", Regional Power, Global Player: Nigeria and the Response to Boko Haram. Issue 3 (2nd October 2019) - Mickler, David; Suleiman, Muhammad Dan; Maiangwa, Benjamin
ABSTRACT: Much of the literature explaining Nigeria's failure to counter the Boko Haram insurgency since 2009 has focused on the country's internal governance, drawing on variations of the "weak state" concept. In this article, we argue that analysts also need to examine Nigeria's international relations for a more critical explanation of why it took over five years to eventually halt the violent group's territorial expansion and regular commission of atrocities. Through analysis of primary documents from various institutions involved in responding to Boko Haram between 2010 to 2015, and elite interviews with academics, security officials and other analysts, this article argues that Nigeria's relatively powerful regional and global positions effectively precluded coercive international intervention and, in doing so, reduced external pressure on Abuja to act more decisively to counter this major threat to security at the human, national and regional levels. Thus, we demonstrate that so-called "weak" states that are simultaneously powerful internationally can manage pressure for action on violence occurring inside their borders.